Positive Relationship Between Precompetitive Sympathetic Predominance and Competitive Performance in Elite Extreme Sports Athletes - Matsumura, Seiji; Watanabe, Ken; Saijo, Naoki; Ooishi, Yuuki; Kimura, Toshitaka; Kashino, Makio (Frontiers in Sports and Active Living, 2021)
Elite athletes achieve superior performance under high pressure in competitive situations. Although it is known that such situations affect the precompetitive activity of their autonomic nervous system (ANS), the relationship between precompetitive ANS activity and performance remains controversial. Especially in extreme sports, it has been shown that cardiac sympathetic tone occurs in athletes before competition attempts. However, the relationship between precompetitive sympathetic tone and performance is unclear. To investigate this relationship in extreme sports, we organized a freestyle snowboard jumping competition and examined competitors' physiological states and performance during this event. The electrocardiograms (ECGs) of 20 elite snowboarders were measured 10 min before each jump in different competitive situations: practice, qualifying, and final sessions. The mean heart rate (HR), the low-frequency to high-frequency component ratio (LF/HF ratio), the logarithm of the HF (lnHF) component of the frequency-domain of the heart rate variability (HRV), the ratio of the standard deviation of all R–R intervals to the root mean square of successive differences of R–R intervals (SDNN/rMSSD ratio), and the rMSSD of the time-domain of the HRV were calculated from the ECG data. The results showed a significant increase in the mean HR as well as significant decreases in the lnHF component and rMSSD of the HRV as the sessions progressed. Interestingly, the mean HR, LF/HF ratio and SDNN/rMSSD ratio of the HRV showed significant positive correlations with competitive scores, and the lnHF component and rMSSD of the HRV showed significant negative correlations with the scores. Our results indicate that precompetitive ANS activity becomes predominantly sympathetic in elite extreme athletes, such as freestyle snowboarders, when the competition intensifies, and that this sympathetic predominance is positively related to competitive performance.